Current status and future application of electrically controlled micro/nanorobots in biomedicine - Pu, Ruochen; Yang, Xiyu; Mu, Haoran; Xu, Zhonghua; He, Jin (Frontiers in Bioengineering and Biotechnology, 2024)
Using micro/nanorobots (MNRs) for targeted therapy within the human body is an emerging research direction in biomedical science. These nanoscale to microscale miniature robots possess specificity and precision that are lacking in most traditional treatment modalities. Currently, research on electrically controlled micro/nanorobots is still in its early stages, with researchers primarily focusing on the fabrication and manipulation of these robots to meet complex clinical demands. This review aims to compare the fabrication, powering, and locomotion of various electrically controlled micro/nanorobots, and explore their advantages, disadvantages, and potential applications.